Impact of capital structure on the operational efficiency of joint stock companies listed on Vietnam stock market - Nguyen, Trong Quyen (H. : ĐHQGHN, 2020)
The paper identifies the impact of capital structure and several other factors (size, growth rate, short-term liquidity solvency) to return ration on average owner's equity of companies in the Vietnam Stock Market, then proposes some solutions to help companies orient in their capital structure determination.